Correct Nutrition Is the Foundation of a Healthy Future - Salomova F.I.; Yuldasheva F.U.; Niyazova O.A; Sherkuzieva G.F (Genius Publishing Group, 2024)
The article provides information about rational nutrition and malnutrition, which is one of the most common problems among people, i.e. eating disorder and its consequences.
Keywords: nutrition; proteins; carbohydrates; fast food